2017
DOI: 10.1597/15-319
|View full text |Cite
|
Sign up to set email alerts
|

Simonart's Band: Its Effect on Cleft Classification and Recommendations for Standardized Nomenclature

Abstract: Responses revealed wide discrepancy in the classification of cleft phenotypes and in the interpretation of the significance of anatomical components in the classification of a cleft lip. We discuss the difficulty in aligning classification based on unclear definition of terms and variable anatomic parameters. We highlight this issue in the face of a need for comparability in clinical evidence-based practices. To ensure precision and uniformity in cleft classification, we recommend that use of the term "Simonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Naran et al conducted a survey on 373 respondents who were members of the American Cleft Palate-Craniofacial Association (ACPA). 12 As many as 87.1% of them agreed that the presence of Simonart's band was a condition that existed in cases of complete cleft lip. The authors suggested that if the soft-tissue band is at or above the line from the alar-facial groove to the columellar-philtral junction, the condition is classified as complete cleft lip, whereas if the soft-tissue band is below the abovementioned line, the condition is classified as incomplete cleft lip.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Naran et al conducted a survey on 373 respondents who were members of the American Cleft Palate-Craniofacial Association (ACPA). 12 As many as 87.1% of them agreed that the presence of Simonart's band was a condition that existed in cases of complete cleft lip. The authors suggested that if the soft-tissue band is at or above the line from the alar-facial groove to the columellar-philtral junction, the condition is classified as complete cleft lip, whereas if the soft-tissue band is below the abovementioned line, the condition is classified as incomplete cleft lip.…”
Section: Discussionmentioning
confidence: 98%
“…The word "Simonart" itself probably comes from "Simonarzt", a combination of Simon and "Arzt" -a German word for doctor. [11][12][13][14] Meanwhile, a Belgian obstetrician Dr. Pierre-Joseph Cécilien Simonart (1816-1846) described congenital bands in children, although he did not specifically describe the congenital band in the lip. [11][12][13] Yet, Simonart's band is more commonly known worldwide to indicate a soft tissue band in cleft lip and palate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of their common embryonic origin, CL and CL+A are significantly different from one another from a clinical point of view, and the clefts may present diverse characteristics associated with their severity. Many classifications have been designed to include the clefts’ different characteristics (Kernahan and Stark, 1958; Kernahan, 1971; Elsahy, 1973; Friedman et al, 1991; Schwartz et al, 1993; Smith et al, 1998; Allori et al, 2017; Naran et al, 2017). One can argue these classifications still do not adequately characterize many features of the clefts, such as magnitude of segment separation (Ortiz-Posadas et al, 2001).…”
mentioning
confidence: 99%
“…The nomenclature committee of the American Cleft Palate Rehabilitation Association has published criteria for an ideal classification and mainly concern certain parameters: Definitions should be concise and clear, a logical distribution with the economy of expression and promotion of academic and clinical research by standardized procedures [3]. Indeed, a simple and comprehensive classification is better accepted scientifically [4]; it must be clearly defined and based on embryological criteria [5] and must allow the establishment of communication, the development of a treatment plan and the comparison of results between the different centers [6]. Since 1922, several classifications of orofacial clefts have been proposed with the aim of generalizing rational criteria allowing communication and exchange between the various practitioners.…”
Section: Introductionmentioning
confidence: 99%